Personality and Inner Conflict of the Main Character in the 2024 Film 1 Kakak 7 Ponakan: A Literary Psychology Study - Anggita Rahma Aprilianti; Lintang Kusumaningrat; Cynara Rahmania; Tommi Yuniawan; Qurrota Ayu Neina (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the personality and inner conflict of the main character, Moko, in the film 1 Kakak 7 Ponakan, using literary psychology theory through a qualitative approach. The film tells the story of Moko's life, who must face major changes after becoming the caregiver for her seven nephews following the death of her older sister. In carrying out her role, Moko is faced with various problems, such as economic pressure, family responsibilities, and the conflict between personal desires and social obligations. This study aims to explain the form of inner conflict experienced by the main character and analyze her personality structure based on Sigmund Freud's psychoanalytic theory, which includes the id, ego, and superego. The results show that Moko experiences inner conflict in the form of a conflict between personal responsibilities and desires, feelings of being burdened but still having compassion, and mental and economic pressure. Furthermore, it was found that the superego is more dominant in Moko, so she tends to prioritize moral values and responsibility over personal interests. This research is expected to provide an understanding of the psychological dynamics of the characters in the film and their relevance to real life, particularly the phenomenon of the sandwich generation.